Shock wave treatment induces angiogenesis and mobilizes endogenous CD31/CD34-positive endothelial cells in a hindlimb ischemia model: Implications for angiogenesis and vasculogenesis - Tepeköylü, Can; Wang, Feng-Sheng; Kozaryn, Radoslaw; Albrecht-Schgoer, Karin; Theurl, Markus; Schaden, Wolfgang; Ke, Huei-Jin; Yang, Yaju; Kirchmair, Rudolf; Grimm, Michael; Wang, Ching-Jen; Holfeld, Johannes (The Journal of thoracic and cardiovascular surgery, 2013)
Shock waves have been shown to induce recruitment of intravenously injected endothelial progenitor cells to ischemic hind limbs in rats. We hypothesized that shock wave treatment as sole therapy would induce angiogenesis in this ischemia model and would lead to mobilization of endogenous endothelial (progenitor) cells. A total of 18 rats, aged 5 weeks old, were subdivided into 3 groups: sham (n = 6), ischemic muscle with shock wave treatment (shock wave treatment group, n = 6), and without shock wave treatment (control, n = 6). Hind limb ischemia was induced by ligation of the femoral artery. Three weeks later, shock wave treatment (300 impulses at 0.1 mJ/mm2) was applied to the adductor muscle; the controls were left untreated. Muscle samples were analyzed using real-time polymerase chain reaction for angiogenic factors and chemoattractants for endothelial progenitor cell mobilization. Fluorescence activated cell sorting analysis of the peripheral blood was performed for CD31/CD34-positive cells. Perfusion was measured using laser Doppler imaging. Functional improvement was evaluated by walking analysis. Angiogenic factors/endothelial progenitor cell chemoattractants, stromal cell-derived factor-1 and vascular endothelial growth factor, were increased in the treatment group, as shown by real-time polymerase chain reaction, indicating the mobilization of endothelial progenitor cells. Fluorescence activated cell sorting analysis of the peripheral blood revealed high numbers of CD31/CD34-positive cells in the treatment group. Greater numbers of capillaries were found in the treated muscles. Blood perfusion increased markedly in the treatment group and led to functional restoration, as shown by the results from the walking analysis. Shock wave therapy therefore could develop into a feasible alternative to stem cell therapy in regenerative medicine, in particular for ischemic heart and limb disease.